Pengaruh Tingkat Pendidikan dan Lingkungan Kerja Fisik Kantor Terhadap Kinerja Karyawan di Dinas Prasarana Jalan Tata Ruang dan Permukiman Provinsi Sumatera Barat - Raf A’ti Rahmawati; Armida S (Universitas Negeri Padang, 2019)
This study was conducted to determine (1) the influence of the level of education and the physical environment of office work on employee performance, (2) the influence of the level of education on employee performance, (3) the influence of the physical environment of office work on employee performance. This research is descriptive associative. The population in this study were employees in Dinas Prasarana Jalan Tata Ruang Dan Permukiman Provinsi Sumatera Barat with 387 employees. The total sample was determined using the Slovin formula and proportional random sampling. From this pattern, 197 employees were obtained as research samples. Data collection techniques used in this study were questionnaires and documentation. The validity test instrument uses Collected Item-Total Colleration and for reliability testing using alpha coefficient formula. The prerequisite test is done by normality test, heteroscedasticity test, and multicollinearity test. The technique used to analyze data is multiple regression analysis. Based on this study, it was found that (1) The level of education and the physical environment of office work have a positive and significant effect on employee performance in Dinas Prasarana Jalan Tata Ruang Dan Permukiman Provinsi Sumatera Barat (2) The level of education has a positive and significant effect on employee performance in Dinas Prasarana Jalan Tata Ruang Dan Permukiman Provinsi Sumatera Barat (3) The physical environment of office work has a positive and significant effect on employee performance in Dinas Prasarana Jalan Tata Ruang Dan Permukiman Provinsi Sumatera Barat Keyword: education level, office physical work environment, employee performance